Development of Similar Materials for Liquid-Solid Coupling and Its Application in Water Outburst and Mud Outburst Model Test of Deep Tunnel - Yanhui Guo; Yi Yang; Zhijun Kong; Jin He (Geofluids)
In order to explore the evolution mechanism of water and mud inrush, based on the fluid-solid coupling similarity theory and a large number of matching tests, fault similar materials with mountain sand, gravel, and red clay as raw materials and surrounding similar rock materials with mountain sand, red clay, cement, and water as raw materials are developed. Similar materials’ physical and mechanical properties and hydraulic properties with different ratios are tested and analyzed. The results show that the red clay content influences the mechanical properties of similar materials and their hydraulic properties, and the gravel substrate mainly influences the fault permeability coefficient. Similar material can be adjusted within a certain range of mechanical parameters. The material is simple and suitable for developing similar materials for different low and medium strength rock masses. Finally, a similar material was used in a model test of the tunnel fault fracture zone to reveal the mechanism of water and mud bursts in the tunnel. The study results can be used as a reference for the development of similar materials for tunnel fracture zone surrounding rocks.